INFORMATION TECHNOLOGY OF CRYPTOGRAPHY-PROTECTED EXPORTS (IMPORTS) OF ROWS OF DATABASE TABLES - Lopin, Ye. B. (Medical Informatics and Engineering, 2018)
Background. Despite the recent developments in eastern Ukraine and complicated economic situation in the state, Ukraine Armed Forces Medical Service is introducing medical information systems for informatization of Ukraine Ministry of Defense healthcare facilities functioning and, in particular, is planning the creation of the medical information system of components of defense forces. At the same time, this project will be performed in low-resource environment with insufficiently developed information infrastructure, shortage of medical service funding and lack of qualified personnel. This article is devoted to the possible solution of the scientific problem of ensuring functioning of territorially (geographically) and structurally scalable information systems in the absence of direct access to global networks (Internet, etc.) by developing and implementing information technology for cryptographic-protected export/import of databases information. Materials and methods. Materials used for research: the database of patients registered and classified as combat casualties of the Military Medical Clinical Center of the Southern Region (Odessa) for the period of 2015-2016; the databases of patients registered and treated in the National Military Medical Clinical Center (Kyiv) and the Military Medical Clinical Center of Occupational Pathology of the Ukraine Armed Forces Personnel (Irpin) patients. For the purposes of this study the developed by the author software and computer equipment that has characteristics similar to the characteristics of the equipment, which is employed in the health facilities of the Ukraine Armed Forces, were utilized. Results. In order to resolve the research task, the information technology for cryptographically-protected export/import of database tables rows has been developed. The developed information technology is presented as the technological processes of an export and import of information. The description of this technology in a form of a list of stages and the algorithms of information processing is in this article. The time intervals of execution of the technological processes of export and import of information from the patients' records databases tables of the Ukraine Armed Forces health facilities have been determined with the developed information technology-based software. The results of these experiments, namely, the average time of export and import, is presented in tables in the article. In order to assess the amount of information that can be exported and imported daily in the medical information system, frequency characteristics of the number of patients who were admitted in the above-mentioned health facilities of the Ukraine Armed Forces. On the basis of the frequency characteristics data, the ranges of values (the number of admitted patients) that include the maximum value and values, which are most often found in the sample, also have been determined. Also, in the article the main directions of application of the developed information technology for the construction of integrated information security systems have been considered. Conclusions. Based on the results of the above studies, conclusions about the advantages and a possibility of daily use of the developed information technology for an export and import of information during functioning of medical information system is formulated. In particular, the main advantages of the developed information technology are: providing with it the possibility of territorial and structural scaling of medical information systems in the absence of access to global information networks (Internet, etc.); suitability and ease using for the construction of integrated information security systems; ensuring a reduction of dependence of informatization projects in military medicine from a underdeveloped information infrastructure of segregate health facilities or their groups.